Comparative Law Between Indonesia And Malaysia In The Resolution Of Cyberbullying Crimes - Rahmawati, Afifah Nur; Sanjaya, Aditya Wiguna (Supremasi Hukum: Jurnal Penelitian Hukum, 2025)
The development of information technology has given rise to various forms of cybercrime, one of which is cyberbullying, which is increasingly prevalent in society. The main problem of this research is how the legal regulations between Indonesia and Malaysia differ in resolving cyberbullying crimes. The purpose of this study is to analyze the similarities, differences, and effectiveness of the legal systems of both countries in providing legal protection to victims. The research method used is a normative-comparative approach by examining the laws and regulations in force in Indonesia, such as the Criminal Code and the Electronic Information and Transactions Law (UU ITE), as well as laws in Malaysia through the Communications and Multimedia Act 1998 and the Personal Data Protection Act. Supporting data is taken from reports of cyberbullying cases in Indonesia and Malaysia in 2024–2025. The results show that Indonesia has a broader legal scope with severe criminal penalties, but its weaknesses lie in the formulation of articles that are open to multiple interpretations and ineffective implementation. In contrast, Malaysia has more specific regulations with practical reporting mechanisms and strong personal data protection, although the criminal sanctions are relatively light. Thus, it can be concluded that Indonesia has a normative advantage, while Malaysia has a practical advantage in addressing cyberbullying.